Exploring the relationship between climate change, air pollutants and human health: Impacts, adaptation, and mitigation strategies - Gibson Owhoro Ofremu; Babatunde Yusuf Raimi; Samuel Omokhafe Yusuf; Beatrice Akorfa Dziwornu; Somtochukwu Godfrey Nnabuife; Adaeze Mary Eze; Chisom Assumpta Nnajiofor (Green Energy and Resources)
The innumerable impact of climate change is a global menace to human health. This paper conveys a comprehensive review of scientific literature to explore the relationship between climate change, air pollutants, and human health. The integral relationship between climate change and health is complex and has a significant impact on every facet of human life. The impact can either be direct (e.g., exposures due to extreme heat, storms, flooding, and air pollution) or indirect (e.g., displacement, food security, and variation in water). The rising temperature of the planet could lead to increasingly severe health impacts from climate change in the future. It is important to take stringent climate actions to mitigate the climate change risk and adapt to the impacts that are already happening. To lessen the speed and severity of climate change, mitigation focuses on cutting greenhouse gas emissions. Options for adaptation include things like advancing to higher ground to stop sea levels from increasing, growing new crops that can grow in a new environment, or using novel construction methods. Investing in novel or enhanced technology, infrastructure, and research is frequently required for adaptation. The review emphasized the importance of considering both short-term and long-term adaptation strategies as well as mitigation efforts, which call for steps to address the root cause by halting or reducing the growth in fossil fuel emissions that might severely and completely increase the earth's scorching temperatures. The results of this study provide insightful viewpoints on adaptation measures, and mitigation strategies for decision-makers, experts in public health, and researchers working in the field of climate change and its effects on human health.